CHARACTERISTIC OF BIODISESEL AND BIODIESEL BLENDING OF OIL LOSSES FROM LIQUID WASTE OF OIL PALM FACTORY - Agus Sundaryono TIN (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACT  The aim of this study was to convert oil losses from palm oil mill (POM) liquid waste into methyl ester. Methyl ester as a result of conversion process was further developed into blending biodiesel. The research was conducted through several stages: 1). insolating oil losses of POM waste which taken from PT Bio Nusantara Bengkulu. Oil losses were degummed and bleached and then the free fatty acid was determined. 2). the conversion process  of oil losses into methyl ester was done through two stages of esterification reactions; using H2SO4 catalyst at 60oC for 2 hours and transesterification using NaOH catalyst at 55oC for 2 hours. 3). Methyl ester was developed as a blending  of biodiesel,  which is a mixture of methyl ester with diesel oil, with the percentages of methyl ester of 25%, 30%, 35%, 40%, and 45%. The yield of methyl ester obtained was 87%. Characterization of methyl ester was done with the following results : 0.858 g/cm3 density, 3.04 cSt viscosity, 3.5% water content, 12.3°C cloud point, 8.3°C pour point, 6.86 mgNaOH/g acid number, 164.4 mgNaOH/g saponification numbers, 108.4% iodine number, and 51.58 cetane number. The parameters do not meet SNI 04-7182-2006 for biodiesel were water  content and acid number. Methyl ester can be developed into blending biodiesel with the characteristic of density, viscosity, cloud point, pour point, saponification number, and cetane number which meet biodiesel standard according to SNI 04-7182-2006.  Keywords: biodiesel, oil losses, methyl ester, waste palm oil mill (POM), transesterification